2022
DOI: 10.1055/a-1896-6154
|View full text |Cite
|
Sign up to set email alerts
|

Acute Corticosteroid Responsive Meningoencephalitis with Cerebral Vasculitis after COVID-19 Infection in a Thirteen-Year-Old

Abstract: Introduction: Various neurologic manifestations have already been described in children during or after severe acute respiratory syndrome coronavirus 2 (SARS-Cov2) infections,. The central nervous system disorders reported in children are mainly encephalopathies during Multisystem inflammatory syndrome (MIS-C). We present here an acute meningo-encephalitis with cerebral vasculitis associated to a COVID-19 infection in a thirteen-year-old girl with a 1-year clinical, EEG and MRI follow-up. Case-report: A thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…It was found that the EEGs of these patients in this study were non-specific, with slow background activity. This result was consistent with previously reported EEG findings in two cases of encephalitis in COVID-19 pediatric patients [ 28 , 29 ]. Moreover, we noted abnormal discharge in the frontal region of the patient suffering from acute encephalopathy syndrome.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that the EEGs of these patients in this study were non-specific, with slow background activity. This result was consistent with previously reported EEG findings in two cases of encephalitis in COVID-19 pediatric patients [ 28 , 29 ]. Moreover, we noted abnormal discharge in the frontal region of the patient suffering from acute encephalopathy syndrome.…”
Section: Discussionsupporting
confidence: 93%